BMP-9 and LDL crosstalk regulates ALK-1 endocytosis and LDL transcytosis in endothelial cells - Tao, Bo (J Biol Chem, 2021)
Bone morphogenetic protein-9 (BMP-9) is a circulating cytokine that is known to play an essential role in the endothelial homeostasis and the binding of BMP-9 to the receptor activin-like kinase 1 (ALK-1) promotes endothelial cell quiescence. Previously, using an unbiased screen, we identified ALK-1 as a high-capacity receptor for low-density lipoprotein (LDL) in endothelial cells that mediates its transcytosis in a nondegradative manner. Here we examine the crosstalk between BMP-9 and LDL and how it influences their interactions with ALK-1. Treatment of endothelial cells with BMP-9 triggers the extensive endocytosis of ALK-1, and it is mediated by caveolin-1 (CAV-1) and dynamin-2 (DNM2) but not clathrin heavy chain. Knockdown of CAV-1 reduces BMP-9–mediated internalization of ALK-1, BMP-9–dependent signaling and gene expression. Similarly, treatment of endothelial cells with LDL reduces BMP-9–induced SMAD1/5 phosphorylation and gene expression and silencing of CAV-1 and DNM2 diminishes LDL-mediated ALK-1 internalization. Interestingly, BMP-9–mediated ALK-1 internalization strongly re-duces LDL transcytosis to levels seen with ALK-1 deficiency. Thus, BMP-9 levels can control cell surface levels of ALK-1, via CAV-1, to regulate both BMP-9 signaling and LDL transcytosis.